(untitled) - Sinclair, John (Glasgow, Geat Britain, 2006)
Collins COBUILD Advanced Learner's English Dictionary offers detailed treatment of today's language. Based on the evidence from the Bank of English corpus, which now contains over 524 million words, the fifth edition contains the most important new words and meanings which have come into the language over the past two years, as well as thousands of new, updated examples, taken directly from the corpus
Keywords: English language; Dictionaries